Antiplatelet therapy - ticagrelor - Giannitsis, Evangelos; Katus, Hugo (Hämostaseologie, 2012)
Ticagrelor, a cyclopentyltriazolopyrimidine (CPTP), is the representative of a new chemical class of P2Y12 receptor inhibitors that differ from thienopyridines (ticlopidin, clopidogrel, prasugrel) as ticagrelor is not a prodrug requiring active biotransformation by cytochromes in the liver and thus is characterized by a more rapid, more effective and more consistent platelet inhibition than ticlopidin or clopidogrel. An extensive study program for dose finding and safety for AZD6140 (DISPERSE studies) and a large-scaled phase III trial (PLATO) were undertaken on more than 18 000 patients for validation of efficacy and safety. In the PLATO trial, patients presenting with the broad spectrum of ACS, i.e. unstable angina, non-STEMI or STEMI, were randomized to ticagrelor (Brilique, Brilinta) or clopidogrel within 24 hours after onset of symptoms, regardless whether they were allocated to a planned invasive or conservative treatment. Compared to clopidogrel, ticagrelor reduced rates of the primary endpoint consisting of cardiovascular death, non-fatal MI, or stroke, without an excess of the primary safety endpoint that was PLATO-defined major bleedings. Results from the pre-specified confirmatory subgroup of patients undergoing planned invasive treatment was consistent with PLATO main trial. In addition, the primary endpoint, as well as CV death and all cause death were consistently reduced with ticagrelor in numerous exploratory subgroups including STEMI patients, those planned for non-invasive treatment, patients undergoing CABG, patients with renal failure, and those with diabetes mellitus, although patients were pretreated before coronary angiography and patients with clopidogrel pretreatment were not excluded. Conclusions: The pharmacological properties and convincing study results of the PLATO trial have stimulated a paradigm change for dual antiplatelet therapy. The new ESC guidelines on the management of ACS without ST segment elevation recommend the use of clopidogrel only when a new antiplatelet drug, e. g. ticagrelor or prasugrel is not available or contraindicated.